The Effectiveness of Environmental Provisions in Regional Trade Agreements - Abman, Ryan (World Bank, Washington, DC, 2021)
Trade liberalization can spur environmental degradation. Concerns over these adverse impacts have led to a debate over the need for environmental provisions in regional trade agreements (RTAs), however the effectiveness of such provisions is unknown. This paper provides new causal evidence that environmental provisions are effective in limiting deforestation following the entry into force of RTAs. It exploits high-resolution, satellite-derived estimates of deforestation and identify the content of RTAs using a new dataset with detailed information on individual provisions. Accounting for the potential endogeneity of environmental provisions in RTAs, the paper finds that the inclusion of specific provisions aimed at protecting forests and/or biodiversity entirely offsets the net increases in forest loss observed in similar RTAs without such provisions. The inclusion of these provisions limits agricultural land expansion, but does not completely offset increases in total agricultural production. The effects are concentrated in tropical, developing countries with greater biodiversity.